2014
DOI: 10.2217/epi.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Architects of the genome: CHD dysfunction in cancer, developmental disorders and neurological syndromes

Abstract: Chromatin is vital to normal cells, and its deregulation contributes to a spectrum of human ailments. An emerging concept is that aberrant chromatin regulation culminates in gene expression programs that set the stage for the seemingly diverse pathologies of cancer, developmental disorders and neurological syndromes. However, the mechanisms responsible for such common etiology have been elusive. Recent evidence has implicated lesions affecting chromatin-remodeling proteins in cancer, developmental disorders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 147 publications
(227 reference statements)
0
46
0
Order By: Relevance
“…It is known that some CHD dysfunction occurs in cancer [37]. In silico analysis in the present showed the higher expression of CHD7 and CHD9 in brain tumor (Additional file 7: Figure S6).…”
Section: Discussionmentioning
confidence: 59%
“…It is known that some CHD dysfunction occurs in cancer [37]. In silico analysis in the present showed the higher expression of CHD7 and CHD9 in brain tumor (Additional file 7: Figure S6).…”
Section: Discussionmentioning
confidence: 59%
“…CHD7 expression predicts survival outcomes in patients with resected pancreatic cancer (Colbert et al ., ). Furthermore, loss‐of‐function mutations in several CHD genes are associated with developmental disorders and intellectual disability (Li and Mills, ). Notably, de novo mutations in CHD7 cause the CHARGE syndrome (coloboma, heart defects, atresia of the choanae, retarded growth and development, genitourinary hypoplasia, and ear abnormalities, including deafness and vestibular disorders), which is characterized by a unique combination of organ anomalies (Basson and van Ravenswaaij‐Arts, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although other CHD proteins have yet to be linked to human genetic disease, it has been demonstrated that CHD4 and CHD5 carry out important functions in neurogenesis [33,34]. Although beyond the scope of this communication, the contribution of CHD dysfunction in the etiology of cancer has been long recognized [35].…”
Section: Chd Family and Genetic Diseasementioning
confidence: 92%